Impact of drug adherence on blood pressure response to alcohol-mediated renal denervation. (31st December 2022) - Persu, Alexandre; Maes, Frédéric; Toennes, Stefan W.; Ritscher, Sabrina; Georges, Coralie; Wallemacq, Pierre; Haratani, Nicole; Parise, Helen; Fischell, Tim A.; Lauder, Lucas; Mahfoud, Felix
Abstract: Purpose: While poor drug adherence is frequent in patients with resistant hypertension, detailed analyses of the impact of drug adherence on the success of renal denervation are scarce. We report drug adherence at baseline, changes in drug adherence, and the influence of these parameters on blood pressure changes at 6 and 12 months in patients treated with alcohol-mediated renal denervation as part of the Peregrine study. Materials and methods: Urinary detection of antihypertensive drugs was performed using high-performance liquid chromatography-tandem mass spectrometry. Full adherence, partial adherence, and complete non-adherence were defined as 0, 1, or ≥2 drugs not detected, respectively. Results: Renal denervation was performed in 45 patients with uncontrolled hypertension on ≥3 antihypertensive medications (62% men, age 55 ± 10 years). At baseline, the proportion of fully, partially, and non-adherent patients was 62% ( n = 28), 16% ( n = 7), and 22% ( n = 10), respectively. At 6 months, adherence improved by 21% ( n = 9), remained unchanged at 49% ( n = 21), and worsened by 30% ( n = 13). Mean 24-h systolic blood pressure decreased by 10 ± 13, 10 ± 4, and 14 ± 19 mmHg in fully, partially, and non-adherent patients ( p = 0.77), and by 14 ± 14, 8 ± 11, and 14 ± 18 mmHg in patients who improved, maintained, or decreased adherence, respectively ( p = 0.35). The results at 12 months were similar. Conclusion: About 40% of patients with apparently treatment-resistant hypertension were not fully adherent at baseline, and adherence decreased further in 30%. Nevertheless, mean blood pressure changes after renal denervation were similar irrespective of drug adherence. Our results suggest that such patients may benefit from alcohol-mediated renal denervation, irrespective of drug adherence. These findings are hypothesis-generating and need to be confirmed in ongoing sham-controlled trials.